Development of E-Module Ecosystem Material in Class V Science Learning in MI/SD - Idayanti, Zulfi; Budiarti, Eriska Witantri; Suleman, Muh. Asharif (UIN Sunan Kalijaga Yogyakarta, 2024)
The development of e-modules has become an innovative solution in enhancing the quality of science learning, particularly in elementary and Islamic elementary schools (MI/SD). This study aims to produce an additional learning resource kind of e-module by using the software flip PDF professional which convert a PDF files become an interactive e-modules that contain an IPA material ecosystem. The e-modules integrates interactive multimedia, visual aids, and self-assessment tool, aligned with the class V curriculum to facilitate independent and active learning without having to wait for the help of educators. This study focuses on the development of an e-module for ecosystem materials in class V. The research employed the 4D model, through several stages, namely: (1) Definition stage: analyzing the 2013 curriculum KI and KD, analyzing questionnaires filled out by teachers from various regions, and problems in the field. (2) Planning stage: compiling the outline of the E-Module, compiling the E-Module framework, compiling the contents of the E-Module, preparing tools and materials, and compiling research instruments. (3) Development stage: validation carried out by material experts and media experts and practicality testing by educational practitioners and students. The E-Module quality assessment from material experts in the first stage received an average score of 3.80 and fell into the